Copper-catalyzed aerobic methyl/methylene oxygenation and C-H formylation with a DABCO-DMSO system for the synthesis of carbonyl indoles and pyrroles - Wang, Yi-Feng (2013)
Copper-catalyzed aerobic methyl/methylene oxygenation of substituted indoles and pyrroles was developed using 1,4- diazabicyclo[2.2.2]octane (DABCO) as an additive in dimethyl sulfoxide (DMSO). Similar aerobic catalytic conditions could also be utilized for direct C–H formylation of C(3) on indoles and C(2) on pyrroles.